Enhancing Customer Satisfaction through Sentiment Analysis and Affect Recognition Using Computer Vision with Predictive Analytics for Blu Water Beach Resort & Parks - Rabano, Carmencita Gadi; Monreal, Richard N. (International Journal of Computing Sciences Research; Vol 8 (2024): Volume 8, 2024)
Purpose — The study aims to use innovative technologies to improve visitor experiences at Blu Water Beach Resort & Parks in Bauang, La Union. Specifically, it intends to create a dynamic website for easy booking and feedback, implement real-time sentiment analysis, use computer vision to evaluate guest behavior and use predictive analytics to provide personalized services. These innovations aim to improve operational efficiency, increase visitor pleasure, and provide useful insights to resort management and the wider hospitality industry. Methodology — Data was collected from respondents via unstructured survey questions. This information informed the development of standardized questionnaires for systematic data gathering. The structured survey results were analyzed using a Likert scale model, which allowed respondents to grade from "Very Satisfactory" to "Very Poor," with points ranging from one to five (1-5). The total points were averaged to determine the Weighted Mean and Average Weighted Mean. Results — The results indicate that innovative technologies would improve customer experience at Blu Water Beach Resort. Tools like sentiment analysis and computer vision with predictive analytics can provide real-time insights into guest satisfaction by interpreting emotions and feedback. This allows the resort to tailor services to better meet guest preferences, leading to higher satisfaction levels. The positive reception to these technologies suggests guests are willing to engage with innovative solutions for a more personalized and responsive service. Conclusion — Blu Water Beach Resort and Parks can enhance guest satisfaction, and service quality, and create memorable experiences by utilizing innovative technologies. This approach will lead to business expansion and success in the competitive hotel industry. Recommendation — The research suggests that employees should receive proper training to understand and effectively use system insights. Encouraging collaboration among guests, workers, managers, and technology partners can foster innovation and enhance visitor satisfaction. Promoting open communication and teamwork is essential for achieving the resort's objectives and improving the overall guest experience. Practical Implication — This research will benefit future researchers, industry colleagues, and competitors by demonstrating the successful integration of IT solutions. The insights can significantly influence the beach resort sector by showcasing how technology can enhance operations and guest experiences.